1962
DOI: 10.1037/h0083255
|View full text |Cite
|
Sign up to set email alerts
|

Figural after-effects: A psychophysical theory of the displacement effect.

Abstract: MANY AFTER-EFFECT PHENOMENA have been reported since Purkinje (1825) and Addams (1834) independently rediscovered the after-effect of seen movement. After-effects were described before 1930 for such diverse perceptual spaces as auditory location (Flugel, 1921;Bartlett & Mark, 1922), repetition rate (Cathcart & Dawson, 1928), pitch (von Bekesy, 1929Cathcart & Dawson, 1929), colour (Cathcart & Dawson, 1929, and geometric size (Cathcart & Dawson, 1929). However, it awaited the now classic paper by Kohler and Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1964
1964
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…The fact that the tactual displacements are larger than the visual is consistent with results from figural aftereffect studies. Taylor (1962) fitted a theoretical equation to the distance paradox data from a number of experiments in auditory, visual, and tactual spaces, and found that the scale parameter of the equation was the same for all the experiments except the single one on tactual width (Charles & Duncan, 1959); for this experiment the scale parameter was about two and a half times larger than that found for the various visual and auditory spaces.…”
Section: Experiments 3 Orientation Of the Radius Of A Semicirclementioning
confidence: 99%
“…The fact that the tactual displacements are larger than the visual is consistent with results from figural aftereffect studies. Taylor (1962) fitted a theoretical equation to the distance paradox data from a number of experiments in auditory, visual, and tactual spaces, and found that the scale parameter of the equation was the same for all the experiments except the single one on tactual width (Charles & Duncan, 1959); for this experiment the scale parameter was about two and a half times larger than that found for the various visual and auditory spaces.…”
Section: Experiments 3 Orientation Of the Radius Of A Semicirclementioning
confidence: 99%
“…The perceived size of the interval is thus increased, or, in another way of looking at the effect, objects appear displaced away from the newly introduced anchor point. The amount of displacement depends, among other things, on the accuracy of perception of the anchor point.It has proved possible in some simple geomeuic situations to use the theory numerically to predict the amount of displacement both as a function of changes in the geometry (Taylor, 1962) and as a function of variation in the precision with which the anchor point may be perceived (Taylor, 1963a). Numerical prediction has not proved possible, however, in situations where two anchor points may be expected to interact, or where there is a well defined zero point on the continuum.…”
mentioning
confidence: 99%
“…It has proved possible in some simple geomeuic situations to use the theory numerically to predict the amount of displacement both as a function of changes in the geometry (Taylor, 1962) and as a function of variation in the precision with which the anchor point may be perceived (Taylor, 1963a). Numerical prediction has not proved possible, however, in situations where two anchor points may be expected to interact, or where there is a well defined zero point on the continuum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there is no quality estimate of the stimuli resulting in the unimodal percepts, and such estimates seem to play a key role when information from different modalities is combined. It has been hypothesized that in the nervous system, different cues are combined in such a way that more reliable cues are given greater weight in the integrated percept; this hypothesis is not new (Taylor, 1962). The hypothesis has of late been experimentally verified in a number of cases (for a recent review, see, for instance, the work of Ernst & Bülthoff, 2004), including the case where the cues are unimodal, such as visual cues for depth estimation (Landy, Maloney, Johnston, & Young, 1995) and cases where the cues are bimodal, such as audiovisual in the ventriloquist effect (Alais & Burr, 2004) and visual-haptic in estimating the height of an object (Ernst & Banks, 2002).…”
Section: The Multimodal Self-organized Networkmentioning
confidence: 99%